Join hands or walk alone? Evidence on lobbying for trade policy in India - Amrita Saha (Asia-Pacific Research and Training Network on Trade (ARTNeT), 2017)
Using primary evidence for 146 Indian manufacturing firms, I examine the types of lobbying strategies for trade policy influence and what drives firm choice for these strategies. Firms can lobby collectively in a group (Join Hands), lobby individually as a single firm (Walk Alone), or adopt a dual lobbying strategy that is a unique combination of collective and individual lobbying. The findings are a first for India, and suggest the following: First, Indian manufacturing firms join hands (lobby using a collective strategy) when targeting sector-wide outcomes in the nature of public goods; firms join hands while walking alone (dual strategy) when targeting product- specific outcomes. Second, the likelihood of adopting a dual lobbying strategy is higher in sectors that are characterized by low concentration (dispersion is higher) such that firms increase their chances of trade policy influence. This suggests a strong competition effect (driving cooperation and individual lobbying) over any free-riding that drives firm strategy to lobby for trade policy influence in India. Finally, availability of resources and lobbying time are significant drivers for the type of strategy undertaken.
Keywords: F13; F14; F5; 330; lobbying strategy; trade policy; India